2011
DOI: 10.1007/s00268-011-1161-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Influencing Postoperative Outcomes of Major Hepatic Resection of Hepatocellular Carcinoma for Patients with Underlying Liver Diseases

Abstract: Careful preoperative selection of patients in terms of the Child-Pugh classification and decrease of intraoperative blood loss are important measures to reduce postoperative morbidity after major hepatic resection in HCC patients with underlying liver diseases. Moreover, we should be aware that preoperative platelet count is independently associated with postoperative morbidity and mortality for those patients following major hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 55 publications
14
131
4
Order By: Relevance
“…The measurement of tumor-specific biological markers can be useful after curative treatments, and it is, therefore, necessary to identify new markers. In addition to tumor-specific markers, liver function, surgical records or outcomes might be closely related to the prognosis of HCC patients after hepatectomy [6][7][8]. We reported that non-tumor related parameters, such as hepatic fibrosis and postoperative long-term ascites, were associated with poor survival [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of tumor-specific biological markers can be useful after curative treatments, and it is, therefore, necessary to identify new markers. In addition to tumor-specific markers, liver function, surgical records or outcomes might be closely related to the prognosis of HCC patients after hepatectomy [6][7][8]. We reported that non-tumor related parameters, such as hepatic fibrosis and postoperative long-term ascites, were associated with poor survival [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Some factors associated with patient survival have been identified [3][4][5]. Markers of poor hepatic function and tumor-related factors are significantly associated with tumor recurrence and lower survival [6][7][8]. Our previous study showed that an advanced grade of hepatic fibrosis, hepatitis, postoperative long-term ascites or postoperative levels of alpha-feto protein (a marker of chronic hepatitis) were significantly associated with shorter survival due to carcinoma after hepatectomy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The rate and amount of PRBCs transfused in patients undergoing liver resections ranges between 8.7% and 85.7% and from 0 to 24 units, respectively [12,[56][57][58][59][60]. In a large series of patients, Katz et al reported that only 18% of patients received blood transfusion [103].…”
Section: Liver Resections and Combined Multivisceral Oncologicmentioning
confidence: 99%
“…Reported estimated blood loss [38][39][40][41][42][43] 400-12,100 2-10 Sacral tumors [44][45][46] 3,000-37,000 0-43 Hemipelvectomy [47][48][49][50] 400-12,100 0-134 Total pelvic exenterations [47][48][49][50] 900-9,500 0-18 Nephrectomy with IVC embolectomy [37,[51][52][53][54][55] 200−16,000 0−91 Liver and multivisceral resection [12,[56][57][58][59][60][61][62] 200->5,000 0-44 Extrapleural pneumonectomies [63][64][65] 900-65,00 0-18 Table 1 illustrates ranges of blood losses and PRBCs of transfused units reported in the literature.…”
Section: Nephrectomy With Inferior Venous Cava Thrombectomymentioning
confidence: 99%
See 1 more Smart Citation